2015
DOI: 10.1007/s00586-015-4050-7
|View full text |Cite
|
Sign up to set email alerts
|

Study investigating the role of skeletal muscle mass estimation in metastatic spinal cord compression

Abstract: Death within 1 year in individuals with spinal metastases is related to lean muscle mass at presentation. Assessment of lean muscle mass may inform decision to operate in patients with spinal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
0
22
1
Order By: Relevance
“…Our results provide new, clinically relevant information to the existing literature regarding the role of sarcopenia on predicting early postoperative outcomes. Gakhar et al and Zhakaria et al have previously reported decreased survival with lower psoas size in patients with spinal metastasis [23,45]. In contrast to our study, Zakaria et al did not examine patients who underwent surgical intervention, but rather those treated with radiation therapy only.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Our results provide new, clinically relevant information to the existing literature regarding the role of sarcopenia on predicting early postoperative outcomes. Gakhar et al and Zhakaria et al have previously reported decreased survival with lower psoas size in patients with spinal metastasis [23,45]. In contrast to our study, Zakaria et al did not examine patients who underwent surgical intervention, but rather those treated with radiation therapy only.…”
Section: Discussioncontrasting
confidence: 59%
“…For each patient, we calculated the ratio of the sum of the left and right psoas muscle area divided by the area of the L3 vertebral body (L3-TPA/VBA) as depicted in Figure 1. This measurement technique was previously shown to have good inter-rater reliability [23]. The timedependent changes in muscle mass in oncologic patients are a well-known phenomenon.…”
Section: Patient and Surgical Datamentioning
confidence: 98%
“…MRI is the most accurate method for determining muscle mass [13]. In all previous studies that diagnosed sarcopenia using CT or MRI, cutoff points were derived arbitrarily, as the lowest tertile or quartile of muscle area [14][15][16][17][18]. In this study, the reference range of TPA for Indian men and women was calculated from records of clinically and radiologically normal adults.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the application is limited to individuals who have had CT scans completed as part of their medical treatment. To date, most published research using CT scans for body composition assessment is retrospective and has been conducted in cancer populations, 12 16 but recent work has extended this to other clinical populations 17 23 …”
Section: Ctmentioning
confidence: 99%
“…Most studies that measure body composition with CT analysis attempt to identify the prognostic ability of skeletal muscle cross‐sectional area, or changes in skeletal muscle attenuation values (ie, HUs) at a single time point 10 , 12 – 21 , 32 35 . In general, skeletal muscle cross‐sectional area and muscle attenuation are often demonstrated to have strong prognostic values—with lower cross‐sectional area or reduced attenuation values being associated with worse outcomes.…”
Section: Ctmentioning
confidence: 99%